STRATEGI PEMBANGUNAN PERKEBUNAN KELAPA DI KABUPATEN ROKAN HILIR - Gulat Medalie Mas Manurung (Universitas Riau, 2004)
In view of national development direction and natural resource potency of Regency Rokan Hilir, henceagricultural sector become economic backbone. Government of Regency Rokan Hilir it is fact that its societyhave to perform persistent effort develop; economic system including development of coconut plantation basedon agroindrustry and agrobisnis. Some supporting reason to make coconut as a prime commodity of RokanHilir Regency are: F